Studi Literatur Pengaruh Pemberian Zinc Terhadap Status Gizi Pada Anak-Anak - Melita Tanjung; William Wibowo; Gracia Winaktu; Marina Rumawas (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
During childhood, rapid growth occurs so that adequate intake is needed to grow optimally, but low appetite is one of the problems often faced. Based on data from WHO (2017), Indonesia is the third country with the highest prevalence of stunted toddlers in Southeast Asia with an average of 36.4% in 2005-2017. One of the causes of lack of appetite and nutrition is zinc deficiency. Therefore, this study review aims to analyze the effect of zinc administration on nutritional status in children. Literature searches were conducted on several databases, namely Pubmed, Google Scholar, and the National Library of Indonesia website. The keywords used were